Use of botulinum toxin in Parkinson's disease. (February 2019) - Jocson, Angeline; Lew, Mark
Abstract: Botulinum toxin has emerged as an important therapeutic intervention within the realm of movement disorders, especially for focal and generalized dystonias. Botulinum toxin has additionally been used for a variety of symptoms associated with parkinsonism. In this review, we will specifically evaluate use of botulinum toxin in idiopathic Parkinson's disease. We will discuss symptoms including sialorrhea, limb, dystonia, tremor, dyskinesias, freezing of gait, camptocormia, pisa syndrome, urinary dysfunction, constipation, dysphagia, eyelid opening apraxia, and blepharospasm.